2021
DOI: 10.3390/su13073803
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Logistic Regression, Information Value, and Comprehensive Evaluating Model for Landslide Susceptibility Mapping

Abstract: This study validated the robust performances of the recently proposed comprehensive landslide susceptibility index model (CLSI) for landslide susceptibility mapping (LSM) by comparing it to the logistic regression (LR) and the analytical hierarchy process information value (AHPIV) model. Zhushan County in China, with 373 landslides identified, was used as the study area. Eight conditioning factors (lithology, slope structure, slope angle, altitude, distance to river, stream power index, slope length, distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 80 publications
(152 reference statements)
0
14
0
Order By: Relevance
“…The deterministic model is based on the principle of slope instability and requires masses of known data, this method needs to be highly simplified and easy to analyze, and it is not suitable for the large-scale research of the LSP [11,12]. The nondeterministic model is based on statistical analysis, with the maturity of GIS technology and rapid computer development; simple algorithms include information model [13], weight-of-evidence model [14], and the analytic-hierarchy process [15]. With the rise of data mining, some more sophisticated algorithms have gradually been used in landslide-susceptibility research, such as the decision-tree model [16], support-vector-machine model [17], and artificial neural networks [18].…”
Section: Introductionmentioning
confidence: 99%
“…The deterministic model is based on the principle of slope instability and requires masses of known data, this method needs to be highly simplified and easy to analyze, and it is not suitable for the large-scale research of the LSP [11,12]. The nondeterministic model is based on statistical analysis, with the maturity of GIS technology and rapid computer development; simple algorithms include information model [13], weight-of-evidence model [14], and the analytic-hierarchy process [15]. With the rise of data mining, some more sophisticated algorithms have gradually been used in landslide-susceptibility research, such as the decision-tree model [16], support-vector-machine model [17], and artificial neural networks [18].…”
Section: Introductionmentioning
confidence: 99%
“…Through comparative analysis, it is found that the same main factors retained both by the LR ao model and the LR bo model include elevation, lithology, land cover, distance from roads, and POI kernel density. Among them, elevation and lithology represent the inoculation factors of landslides, which largely determine the stability of local slopes (Sivakumar and Ghosh, 2021;Tang et al, 2021). In the same way, the materials covered by the ground affect the slope surface, such as runoff and the accumulation of materials on the slope surface.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of a highway landslide disaster is closely related to topography, geological structure, hydrometeorology and human activities, and selecting suitable evaluation factors is the most important part of a landslide susceptibility evaluation, but due to the complexity of the influencing factors, there is no unified selection standard yet [27,28]. A highway, as a typical line-fitting engineering structure, has to traverse different topographic and geomorphological units, especially in mountainous areas, often spreading over slopes, valleys and mountain ranges.…”
Section: Selection Of Evaluation Factorsmentioning
confidence: 99%